Eksistensi Komisi Penyiaran Indonesia Daerah (KPID) dalam Memperkuat Sistem Pengawasan Lembaga Penyiaran dan Materi Siaran - Muslim Ansori (Faculty of Da’wa and Islamic Communication, State Institute for Islamic Studies of Syaikh Abdurrahman Siddik Bangka Belitung, 2019)
Facing the digital revolution era nowadays, where all the information can be easily obtained through our personal mobile phones that can be accessed personally via social electronic media it should be noted whether the contents of the information are inappropriate to be broadcasted and published through electronic media. With the rise of inappropriate information obtained by the public such hoaxes, KPID (Indonesian Broadcasting Commission) as a state institution that regulates all matters related to broadcast ethics must pay attention to the broadcasting and publishing regulations whether they have already been implemented by the media in order to provide good information. This commission can cooperate with other institution to say war against hoaxes. A firm reaction must be taken by KPID to the media that violates broadcast materials regulation. They can be given a warning or revoked their right to broadcast or publish as an action of supervision of the broadcasting media. So, the news given by the media can be justified and also be useful to educate Indonesian society.